2018
DOI: 10.1088/1402-4896/aae719
|View full text |Cite
|
Sign up to set email alerts
|

Tapered fiber liquid crystal hybrid broad band device

Abstract: This paper presents the results of design, manufacturing and characterization of a hybrid broad band filter based on taper technology and liquid crystalline structure using a standard single mode fiber. A liquid crystal mixture, denoted 1550 * , was designed for the electrically driven modulation of an electromagnetic wave at visible range. The main reason for using a biconical optical fiber taper as a core is surrounding it by a liquid crystalline medium providing the possibility to control an effective refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Additionally, the special anti-gravity unit is used because during the elongation process the fiber position is reduced. The signal increase in the anti-gravity system is an impulse for changing drawing velocity, as well as lowering the burner position [11,12]. Additionally, by selection of a proper flame, we can make a taper with a very small dimension of the taper waist.…”
Section: Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the special anti-gravity unit is used because during the elongation process the fiber position is reduced. The signal increase in the anti-gravity system is an impulse for changing drawing velocity, as well as lowering the burner position [11,12]. Additionally, by selection of a proper flame, we can make a taper with a very small dimension of the taper waist.…”
Section: Technologymentioning
confidence: 99%
“…This parameter is described as [9]:From the above formula, it can be concluded that the number of modes propagating in the fiber is also influenced by the wavelength λ and the diameter of the core a. This parameter is important when we want to use a tapered optical fiber [10][11][12] or long period gratings (LPG) [13,14] as an element of optical devices. LCs are built of elongated molecules.…”
mentioning
confidence: 99%